Kinetoplast-associated DNA topoisomerase in Crithidia fasciculata: crosslinking of mitochondrial topoisomerase II to both minicircles and maxicircles in cells treated with the topoisomerase inhibitor VP16. - Ray, D S (1992)
The mitochondrial DNA of the trypanosomatid Crithidia fasciculata consists of thousands of copies of a 2.5 kb minicircle and a small number of 37kb maxicircles catenated into a single enormous network. Treatment of C. fasciculata with the type II DNA topoisomerase inhibitor VP16 produces cleavable complexes of a type II DNA topiosomerase with both minicircles and maxicircles. A combined Southern and Western blot analysis of the cleaved DNA species released from the network by SDS treatment has identified topollmt, the kinetoplast-associated topisomerase, in covalent complexes with linear forms of minicircle and maxicircle DNAs. These results directly implicate topollmt in the topological reactions required for the duplication of the kinetoplast network.